2005
DOI: 10.1182/blood-2004-04-1369
|View full text |Cite
|
Sign up to set email alerts
|

The role of CCL21 in recruitment of T-precursor cells to fetal thymi

Abstract: During embryonic development, T-lymphoid precursor cells colonize the thymus. Chemoattraction by the fetal thymus is thought to mediate T-precursor cell colonization. However, the molecules that attract Tprecursor cells to the thymus remain unclear. By devising time-lapse visualization in culture, the present results show that alymphoid fetal thymus lobes attract Tprecursor cells from fetal liver or fetal blood. CD4 ؊ CD8 ؊ CD25 ؊ CD44 ؉ fetal thymocytes retained the activity to specifically re-enter the thymu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(162 citation statements)
references
References 31 publications
10
146
0
4
Order By: Relevance
“…CCL21 has chemotactic effects on T, B, NK, and dendritic cells (DC) to peripheral lymphatic organs, and participates in several types of immune responses (Riedl et al, 2003;Stein et al, 2003;Liu et al, 2005;Legler et al, 2006;Ashour et al, 2007;Thanarajasingam et al, 2007;Gollmer et al, 2009;Fedele et al, 2011). Ashour et al (2007) reported that subcutaneous injection of CCL21 induced assembly of cytotoxic T lymphocytes (CTL) in draining lymph nodes, mainly the CD3 + , CD8 + , and CD62 -subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…CCL21 has chemotactic effects on T, B, NK, and dendritic cells (DC) to peripheral lymphatic organs, and participates in several types of immune responses (Riedl et al, 2003;Stein et al, 2003;Liu et al, 2005;Legler et al, 2006;Ashour et al, 2007;Thanarajasingam et al, 2007;Gollmer et al, 2009;Fedele et al, 2011). Ashour et al (2007) reported that subcutaneous injection of CCL21 induced assembly of cytotoxic T lymphocytes (CTL) in draining lymph nodes, mainly the CD3 + , CD8 + , and CD62 -subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…In the thymus, CCL25-CCR9 interactions appear to play an important role in the migration of early T cells into the cortex from the subcapsular zone after successful TCR␤ gene rearrangement (4 -7). CCR9 may also play an earlier role in thymic development, either by directly controlling thymic colonization (8 -10) or by participating in thymic precursor development within the bone marrow (BM) 3 (6,11,12).…”
Section: Impaired Accumulation Of Antigen-specific Cd8 Lymphocytes Inmentioning
confidence: 99%
“…This microenvironment provides key signals that support the recruitment of haemopoietic progenitors [3] as well as their subsequent development and selection. Thus, in the adult, the migration of T cell progenitors through thymic cortical regions to the subcapsular area is accompanied by their progression through the CD4 -CD8 -double-negative stages of development, involving differentiation, expansion and antigen receptor gene rearrangement [4,5].…”
Section: Introductionmentioning
confidence: 99%